2019
DOI: 10.1097/aog.0000000000003507
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Capsule Rupture, Postoperative Chemotherapy, and Survival of Women With Stage I Epithelial Ovarian Cancer

Abstract: The incidence and prognostic significance of intraoperative capsule rupture in apparent stage IA-B ovarian cancer varies across histologies, and postoperative chemotherapy was not associated with improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 31 publications
(34 reference statements)
2
38
0
3
Order By: Relevance
“…This is particularly applicable as intraoperative capsule rupture may increase the risk of cancer mortality in certain histology types, especially clear cell. 49 Of stage IC1 disease, 12% of women had recurrence compared to 23% with stage IC2 or IC3 disease (P = 0.02). Studies on FSS in stage II-III disease are very limited given it is not recommended due to recurrence rates that near 40%.…”
Section: Cancer Stagementioning
confidence: 92%
“…This is particularly applicable as intraoperative capsule rupture may increase the risk of cancer mortality in certain histology types, especially clear cell. 49 Of stage IC1 disease, 12% of women had recurrence compared to 23% with stage IC2 or IC3 disease (P = 0.02). Studies on FSS in stage II-III disease are very limited given it is not recommended due to recurrence rates that near 40%.…”
Section: Cancer Stagementioning
confidence: 92%
“…Additionally, complete surgery was not performed on stage I patients; therefore, adhesions with the rectum, bladder, peritoneum, and endometriosis may have remained, which could include microscopic residual lesions. Matsuo et al reported that among apparent stage I EOCs, the clear cell type possesses a disproportionally high risk of capsule rupture during adnexectomy and is associated with the worst prognosis [ 19 ]. However, these findings are limited due to the retrospective nature of the study and the small number of recurrent stage IA/IB (n=6) and stage II (n=20) patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 In a society-based retrospective observational study in Japan for stage IA-1C1 cases in 15 163 EOC patients, including 6107 OCCC cases, OCCC had the highest risk of intraoperative capsule rupture (57.3%) of all the histotypes, and the largest effect of rupture on decreased survival (hazard ratio [HR] = 1.99; 95% confidence interval [CI] 1.45-2.75). 7 The prognostic implications of intraoperative rupture remain unclear, but the importance of intact removal of suspicious adnexal masses was suggested. In lymphadenectomy, Takano et al found a lymph node metastasis rate of pT1 to pT2 tumors of 11% in OCCC.…”
Section: Surgerymentioning
confidence: 99%